Influence of habitat connectivity and seasonality on the ichthyofauna structure of a riverine knickzone - Brambilla,Eduardo M. (2018)
ABSTRACT Knickzones are originated from basaltic outcroppings, present runs, riffles and pools and are highly influenced by flood pulses, which maintain their natural dynamic. However, the construction of hydroelectric power plants alters or eliminate the dynamism of this area and can affect the resident fauna that may be dependent on it. The aim of this study was to evaluate the organization of a knickzone’s ichthyofauna considering the influence of seasonality and connectivity of habitats. The study was performed in a knickzone located in the Sapucaí-Mirim River, Southeast Brazil. We sampled four rocky pools connected to the river and three isolated pools, during rainy and dry conditions. The analysis of the two factors (connectivity and seasonality) and of their interaction showed a significant influence only for seasonality on ichthyofauna structure, with higher values of abundance in the rainy season. The species that most contributed to the high dissimilarity between seasons were Knodus moenkhausii (50% of contribution) and Astyanax bockmanni (21%). The former is the most abundant species in the rainy season and the later in the dry season. The alteration between low and high water level occurs frequently in knickzones, as it is a rocky shallow platform in the middle of a river, with floods occurring seasonally or in stochastic short-term periods. This hydrological seasonal dynamic, high limnological variability and complex interactions of different habitats (pools, runs and rapids) explain the particular ichthyofauna structure in such small area. Our results also indicate the potential importance of basaltic knickzones for regional fish diversity conservation, especially due to the imminent threat by intensive hydropower reservoir construction.